الخطاب الإعلامي الإسلامي - علوان, محمد حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This research tackles an important subject within the informational speech in the Islamic jouralism concerned with talking to the audience in an identity reflecting the Islamic creed. It is a scientific attempt to tackle this and coming up with results which serve the Islamic informational excursing within the margin of the bases , stems, and targets. The study falls in two parts, the first of which is theoretical and the other is practical represented by analysing the content of and the Islamic page. The researcher used the descriptive approach and the style of analysing the content in preparing the study reaching the results. The research comprises there is a reference to the value, the problem, previous works, theses, the approach and the adopted concepts. tackled the subject of journalistic speech and the Islamic speech. subject of information and the informational speech referring to them from the Arab, Islamic, western, informational speech point of view. subject of information speech and calling speech subjects of calling speech elements of communication within the calling speech were also dealt with.